PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN KOMITMEN TERHADAP KEPUASAN NASABAH (Studi Pada PD. BPR BANK DAERAH PATI) - Shinta Nilasari, 13.05.51.0185; Suharmanto, Toto (Students Journal of Economic and Management, 2017)
This Study aimed to analyze the influence of service quality, trust and commitment on customer satisfaction debtor PD. BPR Bank Daerah Pati. The population in this study is the debtor BPR Bank Daerah Pati. Because the population is not known with certainty, then the sampling is based on the formula proposed by Taro in order to obtain a sample of 100 people. Test equipment used in this study testing the validity using factor analisys, reliability using Cronbach Alpha testing and hypotesis using multiple linear regression. The resut of analisys can be concluded that: the positive effect of service quality on customer satisfaction. The better the quality of the service, the customer satisfaction debitor PD.BPR Bank Daerah Pati will increase. Confidence positive effect on customer satisfaction. The better trust then the debitor customer satisfaction PD. BPR Bank Daerah Pati will increase. Commitment positive effect on customer satisfaction. The better trust then the debitor customer satisfaction PD. BPR Bank Daerah Pati will increase. Keywords : quality of service, trust, commitment and customer satisfaction.